2016
DOI: 10.1245/s10434-016-5098-2
|View full text |Cite
|
Sign up to set email alerts
|

Local Recurrence in the Lateral Lymph Node Compartment: Improved Outcomes with Induction Chemotherapy Combined with Multimodality Treatment

Abstract: LatLRs impose a major surgical challenge and result in high LRR and low OS. More R0 resections can possibly be achieved with ICT, which is the only factor that can improve LRR and OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…2 However, there are few studies on the response rate of chemotherapy in LLN recurrence of rectal cancer. Kusters et al 5 reported that 14% of patients with LLN recurrence of rectal cancer achieved pCR by chemoradiotherapy. Thus, treatment for LLN recurrence may be expected to be as effective as synchronous LLN metastasis in rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, there are few studies on the response rate of chemotherapy in LLN recurrence of rectal cancer. Kusters et al 5 reported that 14% of patients with LLN recurrence of rectal cancer achieved pCR by chemoradiotherapy. Thus, treatment for LLN recurrence may be expected to be as effective as synchronous LLN metastasis in rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The available literature regarding induction chemotherapy in addition to chemoradiotherapy for patients with LRRC is limited; currently only three retrospective studies 19 , 36 , 37 have been published. The first study 36 , which focused on patients with lateral local recurrence, reported a high R0 resection rate of 85 per cent in a subgroup of 13 patients who were treated with induction chemotherapy followed by chemoradiotherapy. In the second and third studies 19 , 37 , 58 and 132 patients respectively underwent induction chemotherapy followed by chemo(re)irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…In LRRC patients assessment relies heavily on imaging techniques as in most patients local recurrences cannot be assessed with endoscopy. However, pathological complete response (pCR) rates close to 20% have been described in LRRC [1,5].…”
Section: Introductionmentioning
confidence: 99%